2018
DOI: 10.1166/jnn.2018.15021
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Promising Antitumor Compound Based on Rhodium(II) Succinate Associated with Iron Oxide Nanoparticles Coated with Lauric Acid/Albumin Hybrid: Synthesis, Colloidal Stability and Cytotoxic Effect in Breast Carcinoma Cells

Abstract: In this study, we report the synthesis and characterization of a new rhodium(II) succinate complex (Rh2(suc)4) and its immobilization on lauric acid bilayer-coated maghemite nanoparticles (MGH-2L/Rh2(suc)4) and subsequent adsorption with bovine serum albumin (MGH-2L/Rh2(suc)4/BSA). Rh2(suc)4 has been characterized by elemental analysis, potentiometric titration, TGA, MS, FTIR and UV-Vis analysis. The maghemite phase was confirmed by XRD, and a diameter of 10 nm was obtained by Sherrer equation. The VSM experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Nowadays, this fatty acid has been extensively used in many indurstries, e.g., Food, Medicine, and Daily Chemical etc [23,24]. With the deepening of the related researches, DDA has been found to exert a marked inhibitory effect on the growth of some tumor cells like prostate cancer, breast cancer, stomach cancer and lung cancer [25][26][27]. However, the anticancer effects of DDA against liver cancer cells remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, this fatty acid has been extensively used in many indurstries, e.g., Food, Medicine, and Daily Chemical etc [23,24]. With the deepening of the related researches, DDA has been found to exert a marked inhibitory effect on the growth of some tumor cells like prostate cancer, breast cancer, stomach cancer and lung cancer [25][26][27]. However, the anticancer effects of DDA against liver cancer cells remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The oncostatic effect may be increased by encapsulation to protect LaA from possible degradation in the extracellular environment [171]. LaA may also be used in a coating of nanoparticles to improve intracellular retention and drug delivery [172][173][174].…”
Section: Stearic Acidmentioning
confidence: 99%
“…Despite the myriad of applications of rhodium, limited research has been conducted into the antimicrobial aspect of nanoparticles derived from or containing rhodium. Many studies have shown the antitumor effects of rhodium nanoparticle constructs [131][132][133], catalytic activity [134][135][136], as well as their potential application as detectors [137][138][139]. Although there is limited antimicrobial research in rhodium-derived nanoparticles, the enhanced activity of these materials may indicate an untapped source of antimicrobial treatment for the future.…”
Section: Rhodiummentioning
confidence: 99%